LARGE DISPLACEMENTS OF RIGID-AND-PLASTIC ROUND PLATES RIGIDLY FIXED ALONG THE CONTOUR AND SUBJECTED TO AXYSIMMETRIC LOADING - A V Starov (Structural Mechanics of Engineering Constructions and Buildings, 2011)
The problem of a plastic deforming of a circular plate with rigid pinching edge under act of axisymmetric loading in view of greater bending flexures is observed. The model of ideally plastic body, surface of flow for shells with continuous single-layer cross-section, the kinematic conditions of jointness is used. The analytical solution in a parametric aspect is gained.